An Evaluation of an Online Training Platform for Teaching Positive Emotions for People With Schizophrenia - Nguyen, Alexandra; Frobert, Laurent; Kollbrunner, Aurélien; Favrod, Jérôme (Frontiers in Psychiatry, 2022)
Background: The dissemination of new interventions in clinical practice remains challenging. E-learning may provide wide access in various settings and allow tailored learning trajectories and an adapted training pace. This study evaluates an online platform to train professionals to lead the Positive Emotion Program for Schizophrenia (PEPS) for patients with anhedonia. This study aims to test the reception provided by clinicians to the platform and its perceived usefulness and investigate whether e-PEPS training improves knowledge about the facilitation of PEPS. Materials and Methods: Participants were recruited through advertisements. All participants provided their informed consent on a registration form and completed two pre-test questionnaires, a knowledge test on negative symptoms in schizophrenia, learning strategies and the partnership relationship, and a test on the ability to savor pleasant moments. After the training, they completed the same questionnaire and an evaluation form of the training and its application in personal and professional life. Results: Two-hundred and ten participants were registered to participate into the study, 185 received the access to the platform, and 101 participants completed the training and the post-test assessments. Satisfaction with training was high. The results showed that the participants significantly improved their knowledge about PEPS and increased the skills taught in their personal repertoire after the training. The training allows most clinicians to plan to lead a PEPS group in the year following training. Discussion: As a result of this study, training has been improved and is now freely available to all interested clinicians.